DAMPAK IMPLEMENTASI PERHUTANAN SOSIAL TERHADAP SOSIAL EKONOMI LINGKUNGAN KELOMPOK TANI HUTAN MAHAU LESTARI DESA SUNGAI PENOBAN PROVINSI JAMBI - Zuhdi, Muhammad; Rahmatia, Citra; Kurniawan, Riko (LPPM Universitas Muhammadiyah Jambi, 2024)
Social forestry is a technique of sustainable forest control finished with the aid of nearby or indigenous corporations in areas particular as nation or regular forests, which aims to improve community welfare, but still maintain forest sustainability and environmental balance, as well as socio-cultural dynamics. This research aims to understand the management system and social, financial and environmental benefits of social forestry for Mahau Lestari wooded area Farmer agency (KTH) members in Sungai Penoban Village, Batang Asam District, West Tanjung Jabung Regency, Jambi Province. This study used a purposive sample approach to identify 16 respondents. The study takes an exploratory and descriptive-analytical approach, with records accrued through interviews and focus group discussion. Social Forestry has a positive impact on society in various aspects. The social impact on this forest farmer group is in the form of increasing knowledge of social forestry activities to manage forests. Changes in community behaviour by clearing land without burning and being responsible in protecting forest areas. The perceived economic impact is a contribution to farmer household income of 7.62%. The environmental impact is seen through planting activities with an agroforestry system, and illegal logging is reduced because the community implements a routine patrol system.